3D MODELLING OF A RECONDITIONED PISTON OF A SINGLE-CYLINDER FOUR-STROKE DIESEL ENGINE BY USING SOLIDWORKS SOFTWARE - Isaac, F. O.; Obodeh, O.; Ighodalo, O. (Journal of Mechanical Engineering and Technology (JMET), 2023)
This paper gives the possibility of modelling a reconditioned piston of a single-cylinder four-stroke diesel engine using the ZS1115NM diesel engine specifications. Due to the upsurge of counterfeit spare parts in the market, meeting the original equipment manufacturer (OEM) standards requires a reconditioning process. The reconditioned piston is a thermal barrier coated one with a ceramic material that enables it to withstand high gas combustion temperatures without cracking. A piston converts thermal energy to mechanical energy in an internal combustion engine (ICE). The methodology includes sizing and modelling of the conventional piston, topcoat and bond-coat layers and finally assembling them to get a reconditioned piston using Solidworks Computer-Aided Design (CAD) software. The material chosen for the piston is an aluminium alloy designated as A2618, due majorly to its high coefficient of thermal expansion (CTE) which enables the piston to withstand high thermal stress without cracking or failing. The ceramic material chosen is a 7.5% yttria-stabilized zirconia which is the topcoat with low thermal conductivity and a high coefficient of thermal expansion (CTE) on a bond-coat metallic material called Nickel Chromium Aluminium Cobalt Yttria which are applied by plasma sprayed method on the crown of the substrate. The chosen thickness from the literature of the topcoat layer is 0.35 mm and that of the bond-coat layer is 0.15 mm. Also, from the literature, the major reason for the thermal barrier-coating (TBC) of a diesel engine piston crown using a ceramic material was to improve its performance.